Lowering maintenance immune suppression in elderly kidney transplant recipients; connecting the immunological and clinical dots - Betjes, Michiel G. H.; De Weerd, Annelies (Frontiers in Medicine, 2023)
The management of long-term immune suppressive medication in recipients of a kidney transplant is a poorly explored field in transplantation medicine. Especially elderly recipients are at risk increased risk for side effects and have an exponentially increased risk of infection-related death. In contrast, due to an aged immune system, the risk for acute T-cell mediated rejection is decreased in elderly recipients. Recent advances in allo-immunity research have shown a rapid and substantially decline in polyfunctional high-risk CD4+ T cells post-transplantation. This lowers the direct alloreactivity responsible for T-cell mediated rejection, also known as donor-specific hyporesponsiveness. Chronic antibody-mediated rejection (c-aABMR) is the most frequent cause of kidney graft loss in the long-term. However, in the elderly c-aABMR as cause of graft loss is outnumbered by death with a functioning graft. In addition, DSA development and a diagnosis of c-aABMR plateaus at around 10 years after transplantation resulting in very low risk for rejection thereafter. Intensity of immune suppression regimes could likely be reduced accordingly, but trials in this area are scarce. Tacrolimus monotherapy from one year after transplantation seems feasible in elderly kidney transplant recipients with low immunological risk, showing the expected benefits of less infections and better vaccination responses.